A Thematic Review of Current Literature Examining Evidence-Based Practices and Inclusion - Yvonne L. Goddard; Lindsay Ammirante; Ning Jin (MDPI AG, 2022)
The purpose of this article was to provide a thematic summary of current literature combining the topics of evidence-based practices (EBPs) and inclusive settings. We summarized findings from 27 peer-reviewed articles written in English and published between 2012-2022. A systematic, thematic literature review yielded four broad categories addressed in recent publications: using specific evidence-based practices with PK-12 students, teacher education, teachers' perceptions and attitudes toward including students with disabilities, and collaboration. Within two of those four broad categories, sub-categories also emerged. We discuss the importance of our results and implications for researchers and practitioners.